Kebijakan Dinas Pendidikan Provinsi Banten dalam Pembinaan Tenaga Pendidik Di Sekolah Khusus (Skh) Negeri 01 Kota Serang dan Sekolah Khusus (Skh) Negeri 02 Kota Serang - Mualip, Iip; Amiruddin, Suwaib; Budiati, Ayuning (Universitas Serang Raya, 2024)
This research aims to prove the theory states that the planning, implementation, and evaluation of the policies of the Banten Province Education Service in developing teaching staff in SKh Negeri 01 Serang City and SKh Negeri 02 Serang City. The method used in this research is descriptive qualitative with analytical techniques using various data analyses until reaching a maximum point which is often called the saturation point. According to Sugiyono 2011:37, there are three interactive models in data analysis, namely data reduction, data presentation, and concluding. The location of this research was carried out at three locations, namely the Banten Provincial Education Office in the Special Schools (SKh) sector, the second and third locations were at SKh Negeri 01 and 02 Serang City. This research showed that the curriculum-based training activity program involved 70 participants from teaching staff at state special schools 01 and 02 in the city of Serang with resource persons and the material delivered was per what was needed by teaching staff at special schools. Evaluation of policies in learning training is carried out after the activities are carried out. The evaluation was carried out at the Banten Provincial Education Office. This evaluation is carried out for the sake of improvement for further activities that will be carried out in other places..